2022
DOI: 10.2217/fon-2022-0491
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of EGFR Inhibitors and Radiotherapy in Locally Advanced Non-Small-Cell Lung Cancer: a Meta-Analysis

Abstract: Aim: To assess the efficacy and safety of EGFR inhibitors combined with (chemo)radiotherapy in unresectable, locally advanced non-small-cell lung cancer. Materials & methods: A systematic review and meta-analysis of prospective trials was performed. Results: Twenty-eight studies of 1640 patients were included. In patients harboring EGFR-sensitive mutations, the pooled objective response rate, 1-year overall survival rate and 1-year progression-free survival rate of EGFR-TKIs + (chemo)radiotherapy were 0.80… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…or exon 21 arginine substitution leucine (L858R) mutation. EGFR inhibitors such as Gefitinib, Erlotinib, Afatinib, or Osimertinib play an important role in the treatment of NSCLC patients ( 58 ). However, some studies have shown that the proportion of NSCLC patients carrying EGFR mutations is about 30-40%, and there are still a large number of patients who cannot benefit directly from targeted therapy ( 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…or exon 21 arginine substitution leucine (L858R) mutation. EGFR inhibitors such as Gefitinib, Erlotinib, Afatinib, or Osimertinib play an important role in the treatment of NSCLC patients ( 58 ). However, some studies have shown that the proportion of NSCLC patients carrying EGFR mutations is about 30-40%, and there are still a large number of patients who cannot benefit directly from targeted therapy ( 59 ).…”
Section: Discussionmentioning
confidence: 99%